Stress Analysis of Land Subsidence Effect on Header Pipe 12 Inch in LPG Station Semarang - Taufik Fajar Nugroho; Ede Mehta Wardhana; Ribhi Naufal Azmi (International Journal of Marine Engineering Innovation and Research, 2018)
In the process of distributing LPG to all regions in Indonesia, LPG stations have an important role. In operation, LPG stations may have hazards caused by environmental conditions such as pipe fatigue (fatigue) due to geotechnical forces or failure of components in the system. Research case of piping systems used pipe stress analysis. The purpose of this analysis is to know the deflection of the pipe, the loads that occur by the pipe, and the safety of the pipe and its support. This analysis refers to the code or standard ASME B31.3 where the stress analysis is performed using software. In the process of pipe modeling, there are variations of loading such as pressure load variation, wall thickness and elevation of soil degradation value. From the results of calculation and simulation pipe stress analysis using software can be seen that header pipe 12 inch at LPG station of Semarang is NOT stress, so it is safe to be use. The thickness of the pipe allowed for to be unstable when the operating pressure is greater than 0.15 inch, and the operating pressure allowed for the pipe to be unstable at a thickness of 0.4 pipe (schedule 40) is less than 725 Psi (50 Bars).